Improved High order Euler Method for Numerical Solution of Initial value Time- Lag Differential Equations - Ali, Hayat; Hasen, Saba S. (Iraqi Journal of Science, 2018)
The goal of this paper is to expose a new numerical method for solving initial value time-lag of delay differential equations by employing a high order improving formula of Euler method known as third order Euler method. Stability condition is discussed in detail for the proposed technique. Finally some examples are illustrated to verify the validity, efficiency and accuracy of the method.